'Ulama' al-shari'ah wa-'alaqatuhum bi-al-siyasah al-'Izz ibn 'Abd al-Salam namudhajan (660H) = Shariah scholars and their relationship with politics : a case study of al-'Iz ibn 'Abd al-Salam (660H) / Bara Barakat Hamad al-Gharibeh - al-Gharibeh, Bara Barakat Hamad (2010)
In his thesis, "Shariah Scholars And Their Relationship With Politics: A Case Study of Al-'Iz Ibn 'Abd Al-Salam", the researcher reviewed the involvement of Shariah scholars in politics and their role in power and its elements, and concluded that there is nothing to prevent the Shariah scholars from practicing politics, forming and joining political parties and legislative councils. The researcher explained the concept of politics, and the emergence of political thought and its development in Islam, where Prophet Mohammad-peace be upon him- and his successors explicitly exercised political work. Then, the researcher demonstrated the legal and historical foundation of the involvement of Shariah scholars in politics, and how this involvement was interrupted due to the call of the secularists and modernists who have called for and promoted the separation between religion and politics. Here, the researcher discussed their unsound views by presenting historical examples of the role of Shariah scholars in politics, and the types of relationship that existed between Shariah scholars and Muslim rulers. Next, the researcher reviewed the biography of Imam Al-'Iz Ibn 'Abd Al-Salam including his upbringing, life, virtues and education. The researcher also reviewed his educational journey, his teachers (shjyookh), followers, writings, qualities and noble ethics. After that, the researcher pointed out the involvement of Imam Al-'Iz Ibn 'Abd Al-Salam in politics and governance in his time as well his stands and views concerning these issues. The last part of the research was allocated for the analyses of Imam Al-'Iz Ibn 'Abd Al-Salam political views and the lessons taken from them. And the researcher ended his research with a list of the most important conclusions and recommendations. The results of this research indicate that the withdrawal of Shariah scholars from the field of politics does not have any legitimate reason. Islamic Shariah encompasses all the life aspects: social, economic and political. Today the societies are in dire need for religious and dedicated scholars to save them from backwardness and corruption, and lead them towards dignity and development according to the commands of Allah SWT.